An Unusual Case of Renal Failure Due to Solitary Plasmacytoma: Parenchymal Invasion of the Kidney - ELÇİOĞLU, ÖMER CELAL; OZKOK, Abdullah; Elcioglu, Omer Celal; BAKAN, Ali; SASAK, Gulsah; ATILGAN, Kadir Gokhan; ALISIR, Sabahat; ODABAS, Ali Riza (My University, 2012)
Solitary extramedullary plasmacytoma (EMP) is a rare plasma cell disorder mostly involving the upper airway; however, retroperitoneal infiltration is very rare. Kidney injury associated with EMP is exceptionally rare with only anecdotal reports. Herein we report a case of retroperitoneal EMP causing renal failure by the way of direct renal parenchymal infiltration. Renal parenchymal invasion should be considered in aggressive and refractory plasma cell dyscrasias with unexplained renal failure.